The impact on-the-job (OTJ) training towards employees performance in manufacturing company at Seremban, Negeri Sembilan - Hasyima, Idris (2015)
The aim of this research is to study the impact of OJT (On-The-Job) Training towards employee performance. OJT is a set of independent variable and dependent variable is employee performance. 108 respondents from manufacturing company in Seremban, Negeri was complete the questionnaire. Cronbach’s Alpha (reliability analysis), correlation analysis, regression analysis and descriptive statistics are using to analyze the data that has been collected. The objectives for this research are to study the significant impact of OTJ training to employee performance in manufacturing company. The second objective is to investigate the relationship between OTJ training with employee performance. This is between independent and dependent variables. Result shows that OJT give significant impact towards employee performance in term of their transfer of learning and 3methods (coaching, mentoring, job rotation) positively impact towards employee performance.